2015
DOI: 10.3171/2014.10.peds14250
|View full text |Cite
|
Sign up to set email alerts
|

Reopening of an obstructed third ventriculostomy: long-term success and factors affecting outcome in 215 infants

Abstract: OBJECT The role of reopening an obstructed endoscopic third ventriculostomy (ETV) as treatment for ETV failure is not well defined. The authors studied 215 children with ETV closure who underwent successful repeat ETV to determine the indications, long-term success, and factors affecting outcome. METHODS The authors retrospectively reviewed the CURE Children's Hospital of Uganda database from August 2001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…Other authors have suggested that re-ETV seems worthwhile for patients with late failure of their ETV. 44,45 Furthermore, as has been extensively reported in the literature on initial ETV, we found that 64% of failures occurred within the first 6 months after re-ETV. 21,26,35,42,53,55,63 Another reason for choosing ETV over shunt treatment is the apparent difference in concern among the parents of children with hydrocephalus.…”
Section: Effect Of Timesupporting
confidence: 63%
See 1 more Smart Citation
“…Other authors have suggested that re-ETV seems worthwhile for patients with late failure of their ETV. 44,45 Furthermore, as has been extensively reported in the literature on initial ETV, we found that 64% of failures occurred within the first 6 months after re-ETV. 21,26,35,42,53,55,63 Another reason for choosing ETV over shunt treatment is the apparent difference in concern among the parents of children with hydrocephalus.…”
Section: Effect Of Timesupporting
confidence: 63%
“…One large study from the CURE Children's Hospital of Uganda on 215 pediatric patients reported corresponding findings with a 7-year success for re-ETV of 51%. 45 The population of this group is not necessarily equal to the patient population found in the Western world (e.g., more cases of postinfectious hydrocephalus). The few published studies with 20-40 patients have reported reasonably good success rates between 63% and 81%.…”
Section: Discussionmentioning
confidence: 99%
“…The success of redo ETV following primary ETV has been documented [36,37] ; however, until recently, the utility of redo ETV following ETV/CPC was unknown. In 2015, Marano et al [38] reported a 51% 7-year success rate of redo ETV in a series of 215 patients originally treated with ETV/CPC. Moreover, they were able to identify the following factors as predictors of redo ETV success: history of prior CPC and a delayed time to failure.…”
Section: Etv/cpc Failures Complications and Redo Operationsmentioning
confidence: 99%
“…Moreover, they were able to identify the following factors as predictors of redo ETV success: history of prior CPC and a delayed time to failure. Redo ETV following ETV/CPC was demonstrated to be a worthwhile endeavor given its benefit of avoiding shunt dependence, particularly among patients who experience a late failure, and even in patients with cisternal scarring [38] .…”
Section: Etv/cpc Failures Complications and Redo Operationsmentioning
confidence: 99%
“…Treatment failure was defined as treatment-related death or the need for a second operation for infection or for the recurrence of hydrocephalus. 25 …”
Section: Methodsmentioning
confidence: 99%